Between war and politics : international relations and the thought of Hannah Arendt - Owens, Patricia, 1975- (Oxford : Oxford University Press, 2007)
In this major new assessment of Hannah Arendt's writings on international relations, Patricia Owens provides a compelling case for Arendt's continued relevance to debates about suicide bombing; genocide; the ethics of war; civilian casualties; and the dangers of lies and hypocrisy in wartime.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Arendt, Hannah, -- 1906-1975.; Politics and war; International relations